Application of lean approaches and techniques in an automotive company - Reis, Leandro (2016)
In this paper are applied lean approaches and techniques in an industrial environment at Preh Portugal, Lda., a Company involved in the automotive sector located in Trofa, Portugal. This work makes use of the action-research methodology, aiming to diagnose the production system and to implement lean production procedures in order to optimize the Mizusumashi that supplies several production sections, about plastic Injection, cutting and painting. The results obtained enabled to obtain significant improvements on this Company at several factory management and operational levels.